Perancangan Sistem Informasi Geografis Sekolah Luar Biasa Dengan Metode Extreme Programming - Dendra Pratama Aditian Erlangga; Dian Hartanti; Hendarman Lubis (Journal of Informatic and Information Security, 2022)
Bekasi City is one of the regions located in West Java Province and has a diverse and quality education. However, there are still many Bekasi people who still experience difficulties when they want to find a school location for children with special needs in the Bekasi City area. The purpose of this study is to build a geographic information system in order to make it easier for the peopleof Bekasi to find the location of the Extraordinary School which is in the Bekasi city area. The creation of this website uses the PHP programming language (PHP: Hypertext Preprocessor) with the Codeigniter Framework, XAMPP, and Visual Study Code as text editors. With the method of Developing Extreme Programming systems. The results of this study can be implemented in theform of a website-based geographic information system.